Evidence of Suspicion in Civil Procedure Law: (Study analysis of the use of prejudice as a judge's consideration in decision NoMOR 10/PDT. G/2018/PN. END) - Kartiko, Nafis Dwi; Soegiono, Samuel Putra; Tedjokusumo, Dave David; Siswanto, Carissa Amanda (Universitas Djuanda, 2024)
This study aims to dig deeper into the role of prejudice in the civil law system in Indonesia, by focusing on its definition, types, and impact on judges' decisions. This study specifically discusses the use of suspicion in Decision Number 10/Pdt.G/2018/PN. End, as a case that marks the importance of the role of allegations in resolving civil law disputes. Using normative juridical methods, this study elaborates and examines allegations based on provisions in Burgerlijk Wetboek and HIR, as well as paying attention to secondary legal materials to enrich discussion and analysis of related judicial practices. The findings of this study confirm that the allegation not only acts as prima facie evidence but also reverses the burden of proof that must be borne by those who deny it. This is evidenced by an analysis of the role of allegations in the case that is the focus of the study, showing that the judge has the flexibility to formulate allegations from the facts proven at trial. However, the allegation must meet the criteria set out in Article 173 HIR and Article 1922 of the Civil Code to be considered valid and adequate as evidence.